Attempted Crime and the Crime Drop. (March 2016) - Farrell, Graham
This study contributes to crime drop research on the security hypothesis. Using data from the Crime Survey for England and Wales, it finds that the decline in attempted vehicle-related theft and domestic burglary was delayed by 2–4 years. Between 1993 and 1997, completed domestic burglary fell 21% but attempts by only 2.1%, while between 1993 and 1995 theft of cars fell 8% but attempts increased 3%. The delay is interpreted as consistent with rational choice theory and with some offenders continuing to try, but failing, to complete these crimes when faced with improved security. The subsequent decline in attempts is consistent with offenders, particularly new cohorts of adolescents, having been discouraged.